Evaluation of Systemic Heparin Versus Bivalirudin in Adult Patients Supported by Extracorporeal Membrane Oxygenation. Issue 5 (September 2018) - Berei, Theodore J.; Lillyblad, Matthew P.; Wilson, Kelly J.; Garberich, Ross F.; Hryniewicz, Katarzyna M.
Abstract : Systemic anticoagulation is a standard of care in adult patients supported by extracorporeal membrane oxygenation (ECMO) to prevent circuit thrombosis and subsequent thromboembolic events. Unfractionated heparin has long been considered the anticoagulant of choice, but emerging evidence reports successful ECMO runs with direct thrombin inhibitors. This retrospective study sought to determine whether bivalirudin offers distinct clinical benefits as the anticoagulant of choice in ECMO. Primary end points included thrombotic events during the initial 96 hours of anticoagulation, over the course of their entire ECMO run, and at any time during the admission, as well as in-hospital and 30-day mortality. Secondary end points included percent time within therapeutic range for each anticoagulant, neurologic events, vascular complications, and bleeding. Compared with patients receiving heparin, patients receiving bivalirudin show similar rates of thrombotic events across the three time points (17.9% vs. 9.1 %; p = 0.47, 21.4% vs. 11.4%; p = 0.41, and 25% vs. 22.7%; p = 1.00, respectively). In-hospital (32.1% vs. 36.4%; p = 0.91) and 30-day mortality (32.1% vs. 36.4%; p = 0.91) were no different. Similarly, no differences were observed in percent time within therapeutic range (83.0% vs . 87.7%, p = 0.34), neurological events (7.1% vs . 11.4%, p = 0.99), vascular complications (57.1% vs. 38.6%, p = 0.20), or major (25.0% vs. 45.5%, p = 0.13) and minor (25.0% vs. 22.7%, p = 1.00) bleeding. These results suggest that bivalirudin is a viable alternative to heparin for anticoagulation in ECMO but may not offer a clinically significant advantage as the anticoagulant of choice.